Elevated thyroid autoantibodies as risk factors for metabolic dysfunction-associated fatty liver disease in type 2 diabetes mellitus - Wu, Wenchang; Yang, Ziyi; Li, Owen; Gan, Lulu; Gao, Yue; Xiang, Cheng; Li, Ling; Yan, Yimin (Frontiers in Endocrinology, 2024)
Objective: This study aims to explore the relationship between thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb) levels and metabolic dysfunction-associated fatty liver disease (MAFLD) in patients with type 2 diabetes mellitus (T2DM), providing a theoretical basis for MAFLD prevention and treatment.: From June 2020 to May 2023, 534 T2DM patients were selected from the Endocrinology Department of Xiangyang Hospital affiliated with Wuhan University of Science and Technology. After applying exclusion criteria, 432 subjects were included. Based on abdominal ultrasound and MAFLD diagnostic criteria, subjects were divided into non-MAFLD (n=163) and MAFLD (n=260) groups. Differences in various indicators between the two groups were compared. Correlation analysis assessed the relationship between TPOAb, TgAb, and other indicators, and the prevalence of MAFLD was analyzed under different thyroid function and antibody levels. Multivariate logistic regression identified risk factors for MAFLD in T2DMpatients.According to the FIB-4 index, the group with MAFLD was divided into low-risk (FIB-4 < 1.30, n=150), medium-risk (1.30 ≤ FIB-4 ≤ 2.67, n=100), and high-risk liver fibrosis groups (FIB-4 > 2.67, n=10). Differences in thyroid function and autoantibody levels among the three groups were compared.Results: Compared to non-MAFLD patients, 73.46% of MAFLD patients were overweight or obese, were younger, and had a shorter duration of diabetes. Under normal thyroid function, MAFLD patients had higher levels of TSH, TgAb, and TPOAb (P<0.05). The prevalence of TgAb+, TPOAb+, and TgAb/TPOAb+ was significantly higher at 21.9%, 22.1%, and 29.6%, respectively, with higher prevalence in females. Spearman's correlation showed a positive correlation between TgAb, TPOAb, and AST, and between TPOAb and FINS. MAFLD prevalence varied among quartiles of TSH, TPOAb, and TgAb levels, with significant differences in TPOAb and TgAb components (P<0.05). MAFLD prevalence was positively correlated with TgAb and TPOAb levels. Thyroid autoantibody-positive patients had a significantly higher MAFLD prevalence (P=0.010) at 71.96%. Multivariate logistic analysis found elevated TSH and TPOAb levels as risk factors for MAFLD in T2DM patients [(OR 1.441, 95%